Post-Extractivism: From Discourse to Practice—Reflections for Action - Alberto Acosta (Revue Internationale de Politique de Développement)
The predominant school of thought leads us to believe that an economy without growth is an impossibility and that the only means of achieving development is through economic growth. In turn, this growth requires ever-larger amounts of natural resources to sustain increasing global demand, while generating revenue for the global South to overcome its ‘underdevelopment’. Reality nevertheless tells us that moving beyond this vision is the most pressing challenge of our time: to overcome ‘the religion of economic growth’ and make room for new approaches that will enable us to escape the extractivism ‘trap’. This chapter proposes to move towards a non-capitalist society inspired by the visions, values, experiences and practices of the different forms of buen vivir that can be found among diverse indigenous populations across our planet.